The role of Nrf2 in periodontal disease by regulating lipid peroxidation, inflammation and apoptosis - Ma, Fengyu; Luo, Shangdie; Lu, Chunting; Jiang, Xinrong; Chen, Kexiao; Deng, Jianwen; Ma, Shuyuan; Li, Zejian (Frontiers in Endocrinology, 2022)
Nuclear factor E2-related factor 2(Nrf2) is a transcription factor that mainly regulates oxidative stress in the body. Through Kelch-like epichlorohydrin-related protein -1(Keap1)- nuclear factor E2-related factor 2(Nrf2)- antioxidant response element (ARE) signal pathway, it initiates the expression of several downstream antioxidants, anti-inflammatory proteins and detoxification enzymes, and plays the role of anti-apoptosis, anti-oxidative stress and reducing inflammation. Studies have shown that Nrf2 plays a major role in the regulation of periodontal disease. This review mainly summarizes the role of Nrf2 in periodontal disease by regulating lipid peroxidation, bone homeostasis, inflammation and apoptosis.